# The zeta regularization of \$prod_{m=-infty}^infty (km+u)\$ Answer

Hello expensive customer to our community We will proffer you an answer to this query The zeta regularization of \$prod_{m=-infty}^infty (km+u)\$ ,and the respond will breathe typical by way of documented info sources, We welcome you and proffer you fresh questions and solutions, Many customer are questioning concerning the respond to this query.

The zeta regularization of \$prod_{m=-infty}^infty (km+u)\$

Background: I’m dealing with the computation of the zeta regularization of the innumerable product given by

$$prod_{m=-infty}^infty (km+u)$$

for a actual constructive $$ok$$ and $$Im(u)neq 0$$. From J. R. Quine, S. H. Heydari and R. Y. Song (Example 10) I do know that the zeta regularization of $$prod_{m=-infty}^infty (m+u)$$ is given by

$$prod_{m=-infty}^infty (m+u) = commence{instances}1-e^{2pi i u} & Im(u) > 0 1-e^{-2pi i u} & Im(u) < 0end{instances}$$

so a workable reasoning is as follows:

$$prod_{m=-infty}^infty (km+u) = prod_{m=-infty}^infty ok(m+uk^{-1})$$

Now, utilizing system (1) from J. R. Quine, S. H. Heydari and R. Y. Song we have now that

$$prod_{m=-infty}^infty ok(m+uk^{-1}) = ok^{Z(0)}prod_{m=-infty}^infty (m+uk^{-1})$$

and we’re decreased to computing $$Z(0)$$ the place $$Z(s)$$ is the analytic prolongation of $$Z(s)=sum_{m in mathbb{Z}}(m+uk^{-1})^{-s}$$. We can write $$Z(s)$$ as

$$Z(s) = sum_{m > 0}(m+uk^{-1})^{-s}+(uk^{-1})^{-s}+sum_{m <0}(m+uk^{-1})^{-s}$$

By including and subtracting the $$m=0$$ time period to each of the succession and by altering variable from $$m$$ to $$-m$$ within the sum listed by traverse integers we get

commence{align} Z(s) &= sum_{m=0}^infty(m+uk^{-1})^{-s} – (uk^{-1})^{-s} + sum_{m=0}^infty(uk^{-1}-m)^{-s} &= sum_{m=0}^infty(m+uk^{-1})^{-s} – (uk^{-1})^{-s} + (-1)^{-s}sum_{m=0}^infty(m-uk^{-1})^{-s} &= zeta(s,uk^{-1}) -(uk^{-1})^{-s} + (-1)^{-s}zeta(s,-uk^{-1}) aim{align}

the place $$zeta(s,a)$$ is the Hurwitz Zeta duty. So that by utilizing system 25.11.13 once more in https://dlmf.nist.gov/25.11#E13 we create that

$$Z(0) = dfrac{1}{2}+uk^{-1}-1+dfrac{1}{2}-uk^{-1}=0$$

and we aim up with

$$prod_{m=-infty}^infty ok(m+uk^{-1}) = ok^{Z(0)}prod_{m=-infty}^infty (m+uk^{-1}) = prod_{m=-infty}^infty (m+uk^{-1}) = commence{instances}1-e^{2pi i uk^{-1}} & Im(uk^{-1}) > 0 1-e^{-2pi i uk^{-1}} & Im(uk^{-1}) < 0end{instances}$$

Question: I’m not positive sufficient with these manipulations moving analytic prolongations so I could breathe grievance within the above derivation of $$Z(0)=0$$, Is the above outcome rectify? Does it stay genuine if one replaces the situation $$ok$$ actual and constructive with $$ok$$ a nonzero complicated quantity?

we’ll proffer you the answer to The zeta regularization of \$prod_{m=-infty}^infty (km+u)\$ query by way of our community which brings all of the solutions from a number of dependable sources.